2017
DOI: 10.1038/cddis.2016.235
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid antibodies enhance rat neonatal cardiomyocyte apoptosis in an in vitro hypoxia/reoxygenation injury model via p38 MAPK

Abstract: A significant amount of myocardial damage during a myocardial infarction (MI) occurs during the reperfusion stage, termed ischaemia/reperfusion (I/R) injury, and accounts for up to 50% of total infarcted tissue post-MI. During the reperfusion phase, a complex interplay of multiple pathways and mechanisms is activated, which ultimately leads to cell death, primarily through apoptosis. There is some evidence from a lupus mouse model that lupus IgG, specifically the antiphospholipid (aPL) antibody subset, is path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…The activated MAPK signalling pathway can induce cell death in cancer. 39 Thus, we explored whether this pathway is activated by escin in osteosarcoma. The expression levels of p38, JNK and ERK-2 were determined by western blot analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The activated MAPK signalling pathway can induce cell death in cancer. 39 Thus, we explored whether this pathway is activated by escin in osteosarcoma. The expression levels of p38, JNK and ERK-2 were determined by western blot analysis.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that the JNK/MAPK signaling pathway is associated with various pathophysiological processes during apoptosis and oxidative stress. Bourke et al (50) demonstrated that, in an in vitro H/r injury model, anti-phospholipid antibodies enhanced the levels of apoptosis of newborn rat cardiac myocytes through p38 MAPK. It has previously been observed that myocardial cells were protected from H/r injury through inhibiting JNK (51).…”
Section: Discussionmentioning
confidence: 99%
“…previously described ones (34)(35)(36) with slight modifications. Patient plasma samples diluted to a 50% maximal binding dose and were incubated with either protein C or β2GP1 (0-2.5µM) for 2 hours and subsequently added in duplicate into an ELISA plate coated with β2GPI for 1 hour at room temperature before washed with PBST.…”
Section: Accepted Manuscriptmentioning
confidence: 99%